Loss of heterozygosity induced by a chromosomal double-strand break - Moynahan, Mary Ellen (The National Academy of Sciences of the USA, 1997)
The repair of chromosomal double-strand breaks (DSBs) is necessary for genomic integrity in all organisms. Genetic consequences of misrepair include chromosomal loss, deletion, and duplication resulting in loss of heterozygosity (LOH), a common finding in human solid tumors. Although work with radiation-sensitive cell lines suggests that mammalian cells primarily rejoin DSBs by nonhomologous mechanisms, alternative mechanisms that are implicated in chromosomal LOH, such as allelic recombination, may also occur. We have examined chromosomal DSB repair between homologs in a gene targeted mammalian cell line at the retinoblastoma (Rb) locus. We have found that allelic recombinational repair occurs in mammalian cells and is increased at least two orders of magnitude by the induction of a chromosomal DSB. One consequence of allelic recombination is LOH at the Rb locus. Some of the repair events also resulted in other types of genetic instability, including deletions and duplications. We speculate that mammalian cells may have developed efficient nonhomologous DSB repair processes to bypass allelic recombination and the potential for reduction to homozygosity.